Mapping Informal aActivities in Urban Squares - Zakariya, Khalilah; Harun, Nor Zalina (RMC, IIUM, 2016)
Urban squares are a type of public open space that cater for various activities for the public, such as for events and leisure. The activities in the square are not only contributed by annual events and celebrations, but also daily and weekly informal activities of visitors and tourists, such as leisure strolls, gathering, night picnicking and others. Some squares even become landmarks and focal points of the city. While the design of urban squares has been studied in depth by researchers in other countries, however, a local study that seeks to understand how urban squares are used in Malaysia are still scarce. This research examines three prominent urban squares, which are Dataran Putra, Dataran Merdeka and Dataran Pahlawan, to explore and outline the key criteria that contribute to the activities of the squares. The research objectives are: 1) To map the activities found in the squares and their distributions; 2) To identify the spaces and design elements; 3) To analyse and establish the connections between informal activities, square design and infrastructures; and 4) To recommend design considerations for squares in the Malaysian context. The methods adopted for this research comprise of conducting site inventory and photographic documentation, observation and mapping, and semi-structured interviews with 150 visitors. The analysis reveals that there are five (5) key criteria that contribute to the activities in the urban squares. The criteria consist aspects of planning for strategic location, provision of parking spaces and linkages to public transportations, provision of hard-paved area and open lawn area, provision of shaded and unshaded spaces and provision of functional street furniture and design elements. The research also found that urban squares are significant to the visitors as leisure spaces, urban attractions, and spaces to conduct leisure activities at night. The findings from this research are useful for planners and designer in planning and designing urban squares in Malaysia, or upgrading underutilized urban squares that already exist. This research concludes that an urban square needs to be planned and designed based on its location and context, accessibility and connectivity, infrastructure and design elements, and the subspaces.